Acid-base disorders associated with serum electrolyte patterns in patients on hemodiafiltration - Havlin, Jan; Schück, Otto; Charvat, Jiri; Slaby, Krystof; Horackova, Miroslava; Klaboch, Jan; Sagova, Michaela; Vankova, Svetlana; Matousovic, Karel (Néphrologie & thérapeutique, 2015)
BACKGROUND: Metabolic acidosis (MAC) is a common aspect of dialysis-dependent patients. It is definitely caused by acid retention; however, the influence of other plasma ions is unclear. Understanding the mechanism of MAC and its correction is important when choosing the dialysis solution. Therefore, we assessed the relationship between intradialytic change of acid-base status and serum electrolytes. METHODS: We studied 68 patients on post-dilution hemodiafiltration, using dialysate bicarbonate concentration 32mmol/L. The acid-base disorders were evaluated by the traditional Siggaard-Anderson and modern Stewart approaches. RESULTS: The mean pre-dialysis pH was 7.38, standard base excess (SBE) -1.5, undetermined anions (UA(-)) 7.5, sodium-chloride difference (Diff(NaCl)) 36.2mmol/L. MAC was present in 34% of patients, of which 83% had an increased UA(-) as a major cause of MAC. The mean nPCR was 0.99g/kg/day and correlated negatively with SBE. After dialysis, metabolic alkalosis predominated in 81%. The mean post-dialysis pH was 7.45, SBE 4, UA(-) 2.6, Diff(NaCl) 36.9mmol/L. ΔSBE significantly correlated with ΔUA(-), but not with ΔDiff(NaCl) or ΔCl(-). CONCLUSIONS: MAC in patients on hemodiafiltration is mainly caused by acid retention and is associated with higher protein intake. We did not prove the effect of sodium or chloride on acid-base balance. Even though we used a relatively low concentration of dialysate bicarbonate, we recorded a high proportion of post-dialysis alkalosis caused by the excessive decrease of undetermined anions, which had been completely replaced by bicarbonate and indicated the elimination of undesirable anions, as well as of normal endogenous anions.
Keywords: Electrolytes; elektrolyty; lidé; Kidney Failure, Chronic; mužské pohlaví; Acid-Base Imbalance; hemodiafiltrace; chronické selhání ledvin; Aged; Humans; senioři; Male; poruchy acidobazické rovnováhy; Middle Aged; Hemodiafiltration; lidé středního věku; ženské pohlaví; Female